Revisiting the integration of new members in organizations: an application of the analysis of social networks (Research, Society and Development, 2020)
This article is a version of a paper originally published in the national congress on management excellence. Millions of people around the world are admitted every day to different types of organizations. The management of this process requires the dedication of trained professionals to integrate new members into organizations. Many techniques can be used, however the analysis of social networks, such as Facebook and LinkedIn, has become an increasingly used component by human resources teams. The purpose of this article is to simulate the choice of facilitators in the process of integrating 39 new members of a non-governmental organization. The methodology used relationship information obtained on social networks to analyze according to mathematical techniques of graph theory centrality. As a result, the research selected as facilitators the most well-connected people within the group considering the analysis of different graph centrality indicators. The conclusion is that the group of selected facilitators must allow adding quality, speed and reach to the integration process due to its characteristics of centrality in the network.